2019
DOI: 10.1080/19336950.2019.1608129
|View full text |Cite
|
Sign up to set email alerts
|

Activity of T-type calcium channels is independent of CRMP2 in sensory neurons

Abstract: Amongst the regulators of voltage-gated ion channels is the collapsin response mediator protein 2 (CRMP2). CRMP2 regulation of the activity and trafficking of NaV1.7 voltage-gated sodium channels as well as the N-type (CaV2.2) voltage-gated calcium channel (VGCC) has been reported. On the other hand, CRMP2 does not appear to regulate L-(CaV1.x), P/Q-(CaV2.1), and R-(CaV2.3) type high VGCCs. Whether CRMP2 regulates low VGCCs remains an open question. Here, we asked if CRMP2 could regulate the low voltage-gated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Importantly, in the present study, CBD3063 did not exert an effect on any other voltage-gated calcium channel, which argues for selectivity of our peptidomimetic compound for Ca v 2.2. This is in line with our previous observations that the activity of low-voltage-activated Ca 2+ channels is independent of CRMP2 (Cai, Shan, Zhang, Moutal & Khanna, 2019). We have shown that Cdk5-mediated CRMP2 phosphorylation at residue S522 increases its binding to Ca v 2.2, which leads to an increase in calcium influx (Brittain, Wang, Eruvwetere & Khanna, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, in the present study, CBD3063 did not exert an effect on any other voltage-gated calcium channel, which argues for selectivity of our peptidomimetic compound for Ca v 2.2. This is in line with our previous observations that the activity of low-voltage-activated Ca 2+ channels is independent of CRMP2 (Cai, Shan, Zhang, Moutal & Khanna, 2019). We have shown that Cdk5-mediated CRMP2 phosphorylation at residue S522 increases its binding to Ca v 2.2, which leads to an increase in calcium influx (Brittain, Wang, Eruvwetere & Khanna, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…All electrophysiological recordings were performed using established procedures. Primary cultures of DRG neurons from adult female SD rats (pathogen-free; 140–160 g; Envigo) were made. ,,,,,, Naringenin treatment was applied overnight at 100 μM using 0.1% DMSO as a vehicle control. While relatively high, a concentration of 100 μM naringenin has been previously reported to be needed to detect biological effects including neuroprotection against LPS-induced dopamine neurotoxicity, inhibition of osteoclast formation, induction of anion transport across the rat colonic mucosa, caspase-3 activity in neutrophils, or suppression of prostate tumor cell proliferation .…”
Section: Methodsmentioning
confidence: 99%
“…Inhibitors of VDCC are thus used to treat neuropathic pain, such as Prialt ® [5,36], a synthetic version of µ-conotoxin MVIIA which blocks CaV2.2, or most commonly gabapentinoids like gabapentin or pregabalin [37] which inhibit α2-δ partner protein. CRMP2 (collapsin response mediator protein 2), another partner protein of VDCC (for a review see [38]), has been shown to interact specifically with CaV2.2 and no other VDCC [39] to promote its trafficking and to increase calcium current density [38]. Based on the structure of the calcium channel binding domain (CBD) of CRMP2, CBD peptides have been developed to disrupt CRMP2 interaction with the I-III loop of CaV2.2.…”
Section: Targeting Voltage-dependent Calcium Channel Interactionsmentioning
confidence: 99%